Intensive Care Mortality Prognostic Model for Pediatric Pulmonary Hypertension*. Issue 8 (August 2018) - Balkin, Emily Morell; Zinter, Matt S.; Rajagopal, Satish K.; Keller, Roberta L.; Fineman, Jeffrey R.; Steurer, Martina A.
Abstract : Objectives: The disease burden and mortality of children with pulmonary hypertension are significantly higher than for the general PICU population. We aimed to develop a risk-adjustment tool predicting PICU mortality for pediatric pulmonary hypertension patients: the Pediatric Index of Pulmonary Hypertension Intensive Care Mortality score. Design: Retrospective analysis of prospectively collected multicenter pediatric critical care data. Setting: One-hundred forty-three centers submitting data to Virtual Pediatric Systems database between January 1, 2009, and December 31, 2015. Patients: Patients 21 years old or younger with a diagnosis of pulmonary hypertension. Interventions: Twenty-one demographic, diagnostic, and physiologic variables obtained within 12 hours of PICU admission were assessed for inclusion. Multivariable logistic regression with stepwise selection was performed to develop the final model. Receiver operating characteristic curves were used to compare the Pediatric Index of Pulmonary Hypertension Intensive Care Mortality score with Pediatric Risk of Mortality 3 and Pediatric Index of Mortality 2 scores. Measurements and Main Results: Fourteen-thousand two-hundred sixty-eight admissions with a diagnosis of pulmonary hypertension were included. Primary outcome was PICU mortality. Fourteen variables were selected for the final model: age, bradycardia, systolic hypotension, tachypnea, pH, FIO2, hemoglobin, blood urea nitrogen, creatinine, mechanical ventilation, nonelective admission, previous PICU admission, PICU admission due to nonsurgical cardiovascular disease, and cardiac arrest immediately prior to admission. The receiver operating characteristic curve for the Pediatric Index of Pulmonary Hypertension Intensive Care Mortality model (area under the curve = 0.77) performed significantly better than the receiver operating characteristic curves for Pediatric Risk of Mortality 3 (area under the curve = 0.71; p < 0.001) and Pediatric Index of Mortality 2 (area under the curve = 0.69; p < 0.001), respectively. Conclusions: The Pediatric Index of Pulmonary Hypertension Intensive Care Mortality score is a parsimonious model that performs better than Pediatric Risk of Mortality 3 and Pediatric Index of Mortality 2 for mortality in a multicenter cohort of pediatric pulmonary hypertension patients admitted to PICUs. Application of the Pediatric Index of Pulmonary Hypertension Intensive Care Mortality model to pulmonary hypertension patients in the PICU might facilitate earlier identification of patients at high risk for mortality and improve the ability to prognosticate for patients and families.